KEJADIAN PEROKOK ANAK DI KAMPUNG SELAYAR KOTA MAKASSAR - I MADE SUKARTA; SURIANI B; MARSUKI MARSUKI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Healthy in Health Act No. 36 of 2009 Chapter 1 Article 1 states that health is a state of well-being of body, soul and social that allows everyone to live productively socially and economically. The ASEAN Tobacco Control Report (2019) reveals that more than 30% of Indonesian children start smoking before the age of 10. That number reached 20 million children. (Kurniawati 2019). This fantastic number is based on data on the number of Indonesian children aged 0-14 years based on the 2010 census, which exceeded 67 million people. (Ministry of Health Republic of Indonesia Health Bulletin 2014) General objective of the research,